Digitalisasi Administrasi Publik - Agustin, Rayhan; Jumiati, Jumiati; Januar, Nadila Vhitra; Maharani, Dina Adilla; Septiyena, Elsya Dwi; Saputra, Boni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Abstract In the era of digitalization, the application of digital technology in various aspects of public administration allows internal processes such as data management, communication and archiving to increase efficiency, accelerate the service process and improve accessibility of services for the community. Government initiatives, digital transformation, and the use of technology to create transparent and efficient public services are important in public administration. This study is used to examine the use of technology in creating transparent and efficient public services in the current digital era. Digitalization allows the government to integrate. Information and communication technology into administrative processes, facilitating faster and more accessible public services. However, the application of this technology also presents challenges, such as the digital divide, resistance to change, and data security issues. This transformation requires adaptation in policies, organizational culture, and human resource development so that public administration can meet the needs of society in the digital era. Keywords: Digital transformation, Public Service, e-government, digital divide, data security Abstrak Di era digitalisasi, penerapan teknologi digital dalam berbagai aspek administrasi publik memungkinkan proses internal seperti pengelolaan data, komunikasi dan pengarsipan dapat ditingkatkan efisiensinya, mempercepat proses pelayanan dan meningkatkan aksesibilitas pelayanan bagi masyarakat. Inisiatif pemerintah, transformasi digital, dan penggunaan teknologi untuk menciptakan layanan publik yang transparan dan efisien merupakan hal yang penting dalam administrasi publik. Penelitian ini digunakan untuk meneliti penggunaan teknologi dalam menciptakan layanan publik yang transparan dan efisien di era digital saat ini. Digitalisasi memungkinkan pemerintah untuk mengintegrasikan teknologi informasi dan komunikasi dalam proses administratif, memfasilitasi layanan publik yang lebih cepat dan mudah diakses. Namun, implementasi teknologi ini juga menghadirkan tantangan, seperti kesenjangan digital, resistensi terhadap perubahan, dan isu keamanan data. Transformasi ini menuntut adaptasi dalam kebijakan, budaya organisasi, dan pengembangan sumber daya manusia agar administrasi publik dapat memenuhi tuntutan masyarakat di era digital. Kata Kunci : Transformasi digital, Pelayanan Publik, e-government, kesenjangan digital, keamanan data